Strategic Electronic Government Procurement : Standards Framework - Asian Development Bank; Inter-American Development Bank; World Bank (World Bank, Washington, DC, 2014)
Standards are the infrastructure of commerce. Just as power networks and transport systems are the infrastructure of economic production. The establishment of each of these infrastructures forms a cornerstone for modern economies. It is important that executives and managers be able to appreciate and engage with these issues if the risks to governments are to be managed. Web architects and developers may recoil in horror that government policy and leadership might intrude into these issues. But government is an obvious leader, not suggesting that it should or could regulate such standards, but because of the significance of its choices for its own operations and the weight that these carry in the economy. Government leadership in this area is more often de facto than de jure, but leadership nonetheless, which reflects the reality that government represents more than one third of the economy in most countries. This reality will be of particular significance to developing countries seeking to accelerate the technological activation of their economies and communities.